1983
DOI: 10.5271/sjweh.2392
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of styrene, styrene glycol and more polar styrene metabolites in the mouse.

Abstract: LOF A, GULLSTRAND E, BYFALT NORDQVIST M. Tissue distribution of styrene, styrene glycol and more polar styrene metabolites in the mouse. Scand j work environ health 9 (1983) 419-430. A primary objective of the present investigation was to detennine the tissue distribution of styrene, styrene glycol, and more polar metabolites in mice at different times (0.5-5 h) after the intraperitoneal administration of styrene (3.3 mmoll kg). Another aim was to determine the dose dependence of the metabolite pattern of styr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…The accumulation of total radioactivity after the intraperitoneal administration of 7-[I4C]-styrene agreed well with the results of our earlier study (16). The concentrations of styrene are given in figure 2.…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations
“…The accumulation of total radioactivity after the intraperitoneal administration of 7-[I4C]-styrene agreed well with the results of our earlier study (16). The concentrations of styrene are given in figure 2.…”
Section: Methodssupporting
confidence: 80%
“…Styrene and its metabolites were rapidly distributed in the tissues as has earlier been discussed in detail (16). A possible explanation of the linear dose-response curve for styrene in the pancreas (figure 3) may be related to the route of administration, whereas the deviation from linearity seen for the other tissues may reflect a diminished metabolism at higher doses.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The degree of accumulation of the substances in the various organs could also explain this phenomenon. Tissue distribution studies (Lof et al 1983) have shown that mice intraperitoneal administered styrene accumulate the major level of the substance in fat, followed by the pancreas, liver and kidney. Although styrene is suspected to induce leukaemia among workers engaged in styrene industry there is no report of leukaemia from experimental animal studies.…”
Section: Discussionmentioning
confidence: 99%